Brazilian neurointensive care: a brief history - Sala Domingues, João Roberto; Manno, Edward (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2011)
Neurointensive care arose from the specific growth of the various therapeutic methods in neuroscience, similar to the formation of specific units in other specialties. The progress of the neurological intensive treatment is more recent and because of the high frequency of pathologies in this area it became necessary to structure this specialty in terms of theoretical and physical aspects. In this text, a commentary on the chronology of this development is set out briefly and objectively.
Keywords: Neurointensive care; emergency neurology; neurosurgical intensive care; neuroanesthesiology